Analisis Jaringan VANET Antar Kendaraan Pada Kondisi LOS dan NLOS Menggunakan Metode Single Relay - Munandar, Munandar; Alfina, Alfina (Forum Kerjasama Pendidikan Tinggi, 2022)
The development of transportation technology continues to progress with various models and forms of vehicles that have been produced both on a small scale and on a large scale. The large use of transportation equipment can cause congestion in operating it, one way to reduce this congestion is to use a vehicle-to-vehicle communication system in conditions where there are no obstacles and there are obstacles based on the parameters used through Bit Error Rate and Throuhgput. Vehicular ad hoc network (VANET) is a discipline branch of mobile ad hoc network (MANET) which has the advantage of being able to adapt points to vehicles, markings, signs and buildings. Information exchange on VANET technology communication consists of vehicle to vehicle (V2V) and vehicle to infrastructure (V2I). This study discusses the comparison of VANET networks when there are no obstacles (LOS) and obstacles (NLOS) conditions using Quarature Amplitude Modulation 16 bits per symbol (16-QAM). The use of the single relay method in this study consists of a simulation stage with the MATLAB application and an analysis of the simulation results obtained after carrying out the simulation. The results of this study are a comparison method between vehicles in the single relay network model where the value of the Bit Error Rate without obstacles is BER to distance ratio 〖4.54 x 10〗^(-5), BER to SNR 〖3.00 x 10〗^(-3), BER to speed 〖5.39 x 10〗^(-5). Whereas for Throughput when there are no obstacles, the value of Throughput to distance ratio is 23.750 Mbps, Throughput to SNR is 23.927 Mbps. Throughput to speed of 23.849 Mbps.. Then for comparison when there are obstacles, the value for Bit Error Rate is BER to distance ratio 〖7.17 x 10〗^(-5), BER to SNR 〖3.28 x 10〗^(-3), BER to speed 〖9.56 x 10〗^(-5) and the Throughput value when there are obstacles is the Throughput to distance ratio of 23.486 Mbps. Throughput of SNR 23.920 Mbps, Throughput of speed 23.633 Mbps